2008
DOI: 10.1007/s11126-008-9079-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Mood Disorders in Adults with Developmental Disabilities

Abstract: While the idea that individuals with developmental disabilities (DD) can suffer from mental illness has been largely accepted since the late 1980's, this is still an underserved and poorly studied population. In particular, mood disorders have traditionally been misdiagnosed, under-recognized and poorly treated. Through the years, reported rates of mood disorders in adults with DD have varied widely. Recent epidemiological studies have focused on community samples and find rates of mood disorders from 3 to 8.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 102 publications
0
5
1
Order By: Relevance
“…Most studies of specialized psychiatric assessment in persons with ID have shown that depressive and anxiety disorders tend to be underdiagnosed in the community, and psychotic disorders may be overdiagnosed (Antonacci & Attiah, 2008;Davis, Saeed, & Antonacci, 2008;Hurley, Folstein, & Lam, 2003). Our results showed such a trend for anxiety disorders but fell just short of statistical significance.…”
Section: Discussioncontrasting
confidence: 69%
“…Most studies of specialized psychiatric assessment in persons with ID have shown that depressive and anxiety disorders tend to be underdiagnosed in the community, and psychotic disorders may be overdiagnosed (Antonacci & Attiah, 2008;Davis, Saeed, & Antonacci, 2008;Hurley, Folstein, & Lam, 2003). Our results showed such a trend for anxiety disorders but fell just short of statistical significance.…”
Section: Discussioncontrasting
confidence: 69%
“…As a consequence of these diagnostic challenges, a large part of psychiatric morbidity in people with ID is hidden (Salvador-Carulla et al 2000), which may lead to an undercount in health care among people with ID. For some psychiatric disorders, assessment tools are available, at least for people with mild or moderate ID (Mindham & Espie, 2003; Deb et al 2007; Antonacci & Attiah, 2008; Perez-Achiaga et al 2009; Havercamp & Scott, 2015). For others, researchers have called for further development and evaluation of diagnostic systems for people with ID (Alexander & Cooray, 2003; Moreland et al 2008; Hermans & Evenhuis, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mood disorders represent another common condition in adults with ID. People with a milder type of ID may present with depressive traits that are similar to those observed in the general population; instead, more severely impaired subjects could manifest a low mood with symptoms of anxiety, agitation, and disruptive behaviors [ 117 ]. Anxiety can be present in up to 30% of individuals with ID, who may show both physical and psychological manifestations.…”
Section: A Life Course Perspectivementioning
confidence: 99%